Autonomous Task Planning for Heterogeneous Multi-Agent Systems - Tziola, Anatoli A.; Loizou, Savvas (My University, 2023)
This paper presents a solution to the automatic task planning problem for multi-agent systems. A formal frame-work is developed based on Nondeterministic Finite Automata with -transitions, where given the capabilities, constraints and failure modes of the agents involved, any initial state of the system and a task specification, an optimal solution is generated that satisfies the system constraints and the task specification. The resulting solution is guaranteed to be complete and optimal; moreover a heuristic solution that offers significant reduction of the computational requirements while relaxing the completeness and optimality requirements is proposed. The constructed system model is independent from the initial conditions and the task specifications, eliminating the need to repeat the costly pre-processing cycle, while allowing the incorporation of failure modes on-the-fly. A case study is provided to demonstrate the effectiveness and validity of the methodology.
Keywords: Autonomous agents; Optimization; Specifications